8 months to 5 days: what happened when Pennsylvania changed the vaccination regulations for provisional enrollment?. Issue 5 (3rd May 2020) - Mohanty, Salini; Delamater, Paul; Feemster, Kristen; Buttenheim, Alison M.
ABSTRACT: In March 2017, the Pennsylvania Department of Health reduced the time allowed to demonstrate compliance with school-entry vaccination requirements from eight months to five days. We describe changes in provisional enrollment, vaccine exemptions, and vaccine coverage rates before and after the new regulation. Across Pennsylvania, provisional enrollment decreased from 11.1% in 2016/17 to 2.5% in 2017/18 (77% relative decrease). Personal belief exemptions continued a modest upward trend, similar to previous years, and medical exemptions remained steady. Among kindergartners, coverage with ≥ 2 doses of MMR vaccine and 2 doses of Varicella vaccine increased; similar increases were seen for the MCV and Tdap vaccines among 7th graders. However, improvements in coverage and reductions in provisional enrollment were not consistent across counties. Provisional enrollment in Philadelphia County during the 2017/18 school year (10.4%) did not substantially decrease. The statewide reduction in provisional enrollment suggests that the new regulations accomplished the goal of increasing the proportion of students who are up-to-date on required vaccines at the beginning of the school year without a significant increase in vaccine exemptions. However, the persistence of high provisional enrollment in some counties points to additional barriers to this goal in some schools and regions.